Volar Plate Fixation of Intra-Articular Distal Radius Fractures: A Retrospective Study - Fok, Margaret W. M.; Klausmeyer, Melissa A.; Fernandez, Diego L.; Orbay, Jorge L.; Bergada, Alex Lluch (Journal of Wrist Surgery, 2013)
Background Intra-articular fractures of the distal radius represent a therapeutic challenge as compared with the unstable extra-articular fractures. With the recent development of specifically designed internal fixation materials for the distal radius, treatment of these fractures by fragment-specific implants using two or more incisions has been advocated.Purpose The purpose of this study was to investigate the efficacy of a fixed-angle locking plate applied through a single volar approach in maintaining the radiographic alignment of unstable intra-articular fractures as well as to report the clinical outcomes. We only excluded those with massive comminution, as is discussed in greater detail in the text.Patients and Methods This is a multicentered, retrospective study involving three hospitals situated in Spain, Switzerland, and the United States. In the period between January 2000 and March 2006, 97 patients with 101 intra-articular distal radius fractures, including 13 volarly displaced and 88 dorsally angulated fractures were analyzed. Over 80% were C2/C3 fractures, based on the AO classification. 16 open fractures were noted.Results With an average follow-up of 28 months (range 24–70 months), the range of movement of the wrist was very satisfactory, and the mean grip strength was 81% of the opposite wrist. The Disabilities of the Arm, Shoulder, and Hand (DASH) score was 8. The complications rate was < 5%, including loss of reduction in two patients. All fractures healed by 3 months postinjury.Conclusions Irrespective of the direction and amount of initial displacement, a great majority of intra-articular fractures of the distal radius can be managed with a fixed-angle volar plate through a single volar approach.Level IV retrospective case series
Keywords: distal radius fractures; volar plate; internal fixation; intra-articular fractures